Mechanical reliability of Ce0.8Gd0.2O2−δ‐FeCo2O4 dual phase membranes synthesized by one‐step solid‐state reaction. Issue 4 (6th December 2020) - Zeng, Fanlin; Malzbender, Jürgen; Baumann, Stefan; Zhou, Wenyu; Ziegner, Mirko; Nijmeijer, Arian; Guillon, Olivier; Schwaiger, Ruth; Albert Meulenberg, Wilhelm
Abstract: Ce0.8 Gd0.2 O2− δ ‐FeCo2 O4 composites are attractive candidate materials for high‐purity oxygen generation providing robust chemical stability. Aiming for future industrial applications, a feasible solid‐state reaction process with one thermal processing step was used to synthesize 50 wt% Ce0.8 Gd0.2 O2− δ :50 wt% FeCo2 O4 and 85 wt% Ce0.8 Gd0.2 O2− δ :15 wt% FeCo2 O4 composites. Mechanical reliabilities of the sintered membranes were assessed based on the characterized mechanical properties and subcritical crack growth behavior. In general, the fracture strengths of as‐sintered membranes were reduced by tensile residual stresses and microcracks. In particular, the enhanced subcritical crack growth behavior, which leads to limited stress tolerance and high failure probability after a 10‐year operation, was evaluated in more detail. Further materials and processing improvements are needed to eliminate the tensile stress and microcracks to warrant a long‐term reliable operation of the composites.